Labor Mobility and Innovation in Africa - Linguère Mously Mbaye; Assi Okara; Massimiliano Tani (Institute of Labor Economics (IZA), 2022)
We develop a theoretical model to investigate whether short-term mobility differentially affects innovation in product or process and carry out an empirical analysis with a focus on Africa using firm-level data from the World Bank Enterprise Survey, as well as complementary country level information collected by the World Bank, the World Trade Organisation, and the United Nations. We find that labor mobility positively affects innovation: on average, a 10% increase in the flow of international visits per 10,000 inhabitants is associated with a 0.4 increase in the probability to innovate in products/services or process, supporting the use of labor mobility as an effective mechanism to diffuse productive knowledge and foster innovation. The probability of innovation as a result of short-term mobility is 0.4 higher in Africa overall – especially in East Africa – vis-à-vis the rest of the world, and strongest in the case of innovation in products and services rather than process, suggesting limited capability to produce entirely within the continent. The results are robust to a variety of approaches controlling for endogeneity, which include a control function approach and the use of an instrumental variable based on a gravity model. Focusing only on arrivals for business and professional purposes, our findings show stronger evidence that African firms are more likely to innovate as a result of short-term mobility compared to the rest of the world.
Keywords: F20; F22; J24; J61; O14; O55; 330; innovation; labor mobility; Africa